Photosynthetic Electron Transport in Seeds of a Tropical Seagrass Enhalus koenigii Rich. - Ritchie, Raymond James; Sma-Air, Suhailar (Journal of Fisheries and Environment, 2023)
Enhalus koenigii Rich. (Hydrocharitaceae, Vallisnerioideae) is a widespread monospecific seagrass of the Indian Ocean and West Pacific. The seeds are photosynthetic, an important consideration in their likelihood of successful germination, but their level of photosynthetic activity is not documented. We characterized the photosynthesis and respiration of E. koenigii seeds. Chlorophyll a content of E. koenigii seeds considerably varied, with an average from 13.98±1.25 µg·Chl a·seed-1 or 18.6±2.17 µg Chl a·g-1 FW, while Chl a content of the cone-shaped top part of the seed was 66.5±7.31 mg Chl a·m-2 with Chl b/a ≈ 0.4171±0.0188. Photosynthetic Electron Transport Rates (ETR) of E. koenigii seeds were measured using PAM (Pulse Amplitude Modulation) Fluorescence Technology and the Waiting-in-Line model was used to fit the rapid light curves. The Optimum Irradiance (Eopt) was 366±40.9 µmol photon·m-2·s-1, ETRmax was 230±15.3 (µmol e-·g-1 Chl a·s-1), and photosynthetic efficiency (Alpha, α0) was 1.707±0.222 (e-·g-1 Chl a ·photon-1). Photosynthetic ETR was recalculated as an estimate of Gross Photosynthesis (Pg) based on 4 e- through PSII ≡ 1 O2): Pg-max was ≈ 57.5±3.8 µmol O2·g-1 Chl a·s-1. Respiration rate was measured by O2 electrode in air phase to minimise diffusion difficulties, R = 18.4±3.94 µmol O2·g-1 Chl a·s-1): Pg-max/R ratio at optimum irradiance was ≈ 3.12±0.70, but diurnal net photosynthesis was calculated to be near zero on an intertidal sandflat in a typical diurnal tidal cycle. Photoinhibition of E. koenigii seeds is very severe at sunlight-level irradiances, resulting in photo inhibitory effects >50%.